Health Keeping in the Views of Students: Features and Formation Factors - A. V. Liadova (Высшее образование в России, 2024)
The study deals with the problem of students’ health. Discussing the relevant studies, the author notes that most researchers focus on the role of the educational environment. Considering it, the author underlines that there are other significant factors, which affect students’ health. Because health keeping is a purposeful activity that includes motivational, behavioral, expressive components as well as cognitive one, it is necessary to study the peculiarities of the formation students’ ideas about healthy caring. In addition, it should be taken into account that modern students are digital generation Z, who are famous for their deep involvement into online reality that has a significant impact on the construction of their values and ideas, including those about health. The purpose of the paper is to study the ideas about health keeping among Zet-students and identify the factors of their formation. The theoretical and methodological background includes theories of social constructivism, digitalization of health and mediatization. The empirical data consist of data from the author’s research (methods – survey (online questionnaire)) and those presented in relevant publications. Based on the results, the features of ideas about health keeping and the main factors of their formation were identified. As it has found out, along with traditional ones, this process is increasingly influenced by online resources, which have ambivalent impact. Considering the focus of Generation Z students on healthy life, health value, it is proposed to expand measures within the educational process to form an ideology of healthy lifestyle among modern students.